Development of PJBL-Based Physics Edu Media to Improve The 21st Century Learning Skills of High School Students - Paminto, J.; Yulianto, A.; Linuwih, S. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
The purpose of this research was to create physics teaching resources that would enhance students' 21st century skills in renewable energy. The RD approach was used in conjunction with data collection methods including both test and non-test modes. This study involved three validators who assessed the learning materials from the perspectives of both material and media aspects. According to the assessment results, the material aspect received a rating of 'very good,' whereas the media aspect scored 'good.' The enhancement of 21st century learning competencies was gauged through pretest and posttest evaluation, revealing a rise in critical thinking, creativity, communication, collaboration, use of ICTs, as well as life and career skills. The study determined that the PjBL-Based Physics Edu learning materials could serve as a reliable instructional tool for teaching renewable energy topics with moderate effectiveness.